Letter regarding BS in Data Science degree program at CSU Channel Islands - Nathan S. Evans:::Deputy Vice Chancellor, Academic and Student Affairs::: (2024)
No abstract available. A letter from Nathan S. Evans, Ed. D. to President Richard Yao, Ph.D. approving the Bachelor of Science degree program in Data Science, effective fall 2025.